A Descriptive Study of Customer’s Opinions on Factors Influencing Purchasing Decisions in Corporate Retail Stores in a City of Vijayawada. - Anusha, S.; Satish Kumar, D.; Bindu, P.; S. Rao, D.; Niranjan, H. (International Journal of Engineering and Technology, 2018)
Corporate retail stores are today the focal points for purchasing decisions of middle and high-income groups in urban India. However, each corporate retail store has its own model of retailing. Storing different varieties of products at same locality, location advantage, self-servicing outlets, window shopping, large scale discount, specialty stores are some of the models retailing stores adopted, but all these retail models are not beingÂ Â popular among the consumers. Consumerâ€™s preferences and choices are varying across different retail models. In this context the present study wants to explore significant difference among corporate retail stores in Vijayawada in consumer preference and choices.Â Â Â